The impact of temporary uses on property prices: the example of food trucks. Issue 1 (2nd January 2017) - Freybote, Julia; Fang, Yiping; Gebhardt, Matthew
Abstract: Food trucks represent a temporary use of vacant or underutilised land. They have been assumed to increase the livability, vibrancy and attractiveness of a neighbourhood. However, no previous study has investigated whether this effect is reflected in property prices within the surrounding neighbourhood. We investigate the impact of a food truck pod on the values of single-family homes nearby. Using a quasi-experimental design, transaction data from Portland, Oregon and a difference-in-difference specification of a spatial regression model, we find that food trucks actually represent a negative externality, and that proximity of a home to food trucks is penalised by homebuyers. The closer a home is to the food trucks, the lower is the sales price. Explanations for this effect include increased parking shortages and trash issues in a neighbourhood due to food truck visitors.